ROLE OF MAHATMA GANDHIJI ON INDIAN NATIONAL MOVEMENT - Madhavi Ramagiri, Dr. Siraj Khan (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Mohandas Karamchand Gandhi (1869-1948), here in after Gandhiji, was undoubtedly the most authentic and celebrated representative of the wisdom and culture of India in our times. His countrymen address him, with respect, as the Mahatma. For Many, among the greatest, Gandhiji was the great. He was a social reformer, an economist, a political philosopher and a seeker of truth. We consider him as a 'yugapurusha', one who inaugurated a new era. The contribution of Mohandas Karamchand Gandhi to the Indian national movement was un-paralleled. He made the Indian National Congress a peoples 'Congress and the national movement a mass movement. He made people fearless and bold and taught them the non-violent method for fighting against injustice. He had a passion for individual liberty which was closely bound with his understanding of truth and self-realization. He played a pivotal role in the India’s struggle for freedom which was the world’s largest democratic movement. Indian nationalism achieved its highest peak under Gandhi’s leadership.Gandhiji's role in the National Movement of India was undoubtedly the most remarkable. Front 1919 to 1947 A.D. The father of the Nation Mahatma Gandhi was one of these great men who dedicated their whole life to the service of the mankind.